VIRTUALIZATION AS A MEANS OF TRANSFORMING THE SPACE-TIME CONTINUUM OF MODERN MEDIA ADVERTISING - Elena N. Yezhova; Nikolai S. Chernov (Вестник Северо-Кавказского федерального университета)
This article discusses the basic techniques of transforming the space-time continuum of modern media advertising, analyzes the impact of virtual reality on the mediaadvertising image of the world, and describes the causes of the phenomenon of virtualization advertising space and time.